The Validation of Rectangular Sharp Crested Weir Flow using ANSYS – FLUENT - Bruska S. Mamand; Pshtiwan O. Zaid (Zanco Journal of Pure and Applied Sciences, 2024)
A weir is a structure consisting of an obstruction such as a dam that built across the open channel to change its flow characteristics. In the present study, a total 12 experiments were done in the laboratory of civil engineering department inside an open channel with 20 cm width and installing full width rectangular sharp crested weirs. Then the numerical runs were validated with experimental findings and additional runs were done. The implementation of Numerical Methods A volume of fluid (VOF) model was created for the situation when water and air are in direct contact with one another. Three distinct k-epsilon turbulence models were examined [standard, RNG, and realizable]. According to mass balance data, the greatest error in experimental measurements between the main channel's input and outlet discharges does not exceed 9.542%. Furthermore, average percentage of error between numerical and experimental outlet discharges for standard, RNG and realizable k- epsilon method was 7.235, 5.489 and 7.301 respectively. Cd increased with increasing the ratio of (H1/P). The water surface will be stable along 2 m of upstream channel length upstream of the sharp crested weir, and the longitudinal water levels will decrease slightly over the weir with a curved profile, as determined experimentally and numerically.